Causes and effect of delays in Aceh construction industry - Majid, Ibnu Abbas (2006)
One of the most common problems in the construction project is delays. Delays of a construction project can be defined as the late completion of works as compared to the planned schedule or contract schedule. Projects can be delayed due to number of reasons that may be due to the client, the contractor, acts of God, or a third party. They may occur early or later in the project development, alone, or with other delays. Delays can be minimized only when their cause are identified. The objective of this study was to identify the major causes of delays, the effects of delays, and methods of minimizing delays in construction project. This study was carried out based on literature review and a questionnaire survey. A total of fifty seven factors and eight groups that contributed to the causes of delay, the six factors that effects delays and thirty five methods of minimizing construction delays were identified based on literature review. The questionnaire survey was distributed to the targeted respondent in Aceh, Indonesia construction industry. The objectives of the study have been successfully achieved. The top ten most important factors that contributed to the causes of delays, i.e., insufficient numbers of equipment; inaccurate time estimate; monthly payment difficulties; changes orders; inaccurate cost estimate; poor site management and supervision; inadequate modern equipment; shortage of construction materials; incompetent project team; improper project planning and scheduling; and contractor’s financial difficulties. Contractor-related delays was ranked the most significant groups that cause delays, followed by equipment-related delay, client-related delays, material-related delays, financerelated delays, consultant-related delays, external-related delays, and labor related delays. Time and cost overrun were the common effects of delays in construction projects. To minimize delays in construction projects it has been identified that the top ten most effective methods of minimizing construction delays includes: ensure adequate and available source of finance until project completion; competent project manager; availability of resources; frequent progress meeting; awarding bids to the right/experience consultant and contractor; use of experienced subcontractors and suppliers; multidisciplinary/competent project team; accurate initial cost estimates; competent and capable of clients representative; use of appropriate construction methods; performs a preconstruction planning of project task and resources needs; and project management assistance